Compliance with temperature and time requirements during in-hospital distribution of blood components: A national survey among transfusion services. (December 2020) - Castrillo, Azucena; Arroyo, José L; Romón, Íñigo; Rivera, José
Highlights: Temperature and time during in-hospital distribution of BC affect quality and safety. 41 % of the Spanish Transfusion Services apply the 30-minute rule to discard RBC. 82 % of the Spanish TS accept PC to stock after being outside up to 60 min. Laxer requirements for intra-hospital distribution would reduce BC loss. A revision of current Guidelines on BC management is necessary. Abstract: Introduction: Temperature and time conditions during storage and distribution of blood components (BC) and their permissible deviations are strictly regulated. The degree of compliance with these requirements in daily practice of transfusion services (TS) is not well known. Materials and methods: We conducted a survey among Spanish hospital TS covering different aspects of BC management in their daily activity. Results: Eighty-three TS managing 56 % of total transfusions answered the survey. Monitoring of red blood concentrates (RBC) temperature during in-hospital distribution was routinely performed by only 12 % of the TS. The main criterion for BC re-entry into the stock was the total time spent outside controlled temperature. Up to 41 % of the TS apply the "30-minute rule" to distributed RBC, while most services use a 60-minute rule for PC. No adverse events were detected when RBC that had remained longer than 30 or 60 min outside the TS were transfused. Fresh frozen plasma is usually thawed 2 h preissue and stored at 4 °C up to 24 h. Discussion and conclusions: In the Spanish context, the 30- and 60-minute rules for re-entry of RBC and PC into the TS stock are loosely followed. Feedback for a large number of TS suggests that the extension of the 30-minute RBC rule to at least 60 min is feasible, if other safety requirements are met. Flexibility with some requirements could help reduce product loss without deleterious effect on BC safety.